2016
DOI: 10.33546/bnj.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Massage and Aromatherapy on Stress and Prolactin Level Among Primiparous Puerperal Mothers in Semarang, Central Java, Indonesia

Abstract: Background: Exclusive breastfeeding in Semarang during the past five years remains low. Only 20 to 64% of mothers were breastfed exclusively in 2010-2012. The incidence of postpartum blues was reported by 29.9% mothers, and mostly (56.6%) was primiparous.Objective: This study aims to determine the effect of Loving Massage, aromatherapy, and a combination of Loving Massage and aromatherapy on stress levels, and changes in levels of prolactin in primiparous puerperal in Semarang.Method: A true experimental study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Rahayu et al (2018) stated that endorphin massage by husbands could lower the anxiety of postpartum mothers. Melyana et al (2016) also found that the combination of loving massage and effective aromatherapy could improve the prolactin hormone levels of postpartum mothers [21]. This hormone increases the breast milk production of the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Rahayu et al (2018) stated that endorphin massage by husbands could lower the anxiety of postpartum mothers. Melyana et al (2016) also found that the combination of loving massage and effective aromatherapy could improve the prolactin hormone levels of postpartum mothers [21]. This hormone increases the breast milk production of the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature suggests that lavender oil has a comforting effect on the central nervous system, and a massage with lavender oil can increase milk production and prolactin levels in mothers [ 115 , 116 , 117 ]. A combination of aromatherapy and massage using EOs increased milk production to a larger extent, as compared to individual treatments [ 118 ]. Similarly, jasmine oil has been observed to increase milk secretion [ 119 ].…”
Section: Therapeutic Effects Of Eosmentioning
confidence: 99%
“…Massage Effleurage Pada Punggung Ibu Menyusui Pijatan terbukti mampu mengurangi stress dan meningkatkan level prolaktin pada ibu menyusui (Widyawati et al, 2016). Massage Effleurage dilakukan dengan cara menekan jaringan dengan kedua telapak tangan dimulai dari pinggang sampai bahu (Hanief et al, 2019).…”
Section: Massage Effleurageunclassified